Alien agency: Experimental encounters with art in the making - Salter, Chris (Massachusetts Massachusetts institute of technology, 2015)
In Alien Agency, Chris Salter tells three stories of art in the making. Salter examines three works in which the materials of artthe stuff of the worldbehave and perform in ways beyond the creators intent, becoming unknown, surprising, alien. Studying these worksall three deeply embroiled in and enabled by science and technologyallows him to focus on practice through the experiential and affective elements of creation. Drawing on extensive ethnographic observation and on his own experience as an artist, Salter investigates how researcher-creators organize the conditions for these experimental, performative assemblagesassemblages that sidestep dichotomies between subjects and objects, human and nonhuman, mind and body, knowing and experiencing.Salter reports on the sound artists Bruce Odland and Sam Auinger (O+A) and their efforts to capture and then project unnoticed urban sounds; tracks the multi-year project TEMA (Tissue Engineered Muscle Actuators) at the art research lab SymbioticA and its construction of a hybrid semi-living machine from specially grown mouse muscle cells; and describes a research-creation project (which he himself initiated) that uses light, vibration, sound, smell, and other sensory stimuli to enable audiences to experience other cultures ways of sensing. Combining theory, diary, history, and ethnography, Salter also explores a broader question: How do new things emerge into the world and what do they do?